Once upon a time. The complete fourth season [videorecording (DVD)] - Horowitz, Adam, 1971-; Kitsis, Eddy (2015)
Soon after Emma and Hook unwittingly bring Elsa of Arendelle to Storybrooke, they encounter the mysterious "Snow Queen," whose relentless obsession with both Emma and Elsa has chilling consequences. Meanwhile, it appears Regina has at last found true love with Robin Hood, but how will she react when her happy ending is thwarted yet again by a maddening, seemingly pre-ordained twist of fate?